5. Didactic Strategies for the Development of Professional Musical Hearing - Duţică Luminiţa (Review of Artistic Education, 2016)
This study suggests an incursion into the issue of the development of professional musical hearing, which is divided into three major sections. Starting from the general to the particular, this approach starts with defining the field of reference - musical hearing, seen as a prerequisite in the training of future artists. Closely related to the curricula and textbooks from the pre-university vocational education, the subject Music Theory - Solfeggio - Dictation holds the conceptual and pragmatic frame on the basis of which we offered different solutions for the development of musical hearing. In this respect, I focused my research on the following typologies: melodic, polyphonic, harmonic, dynamic, timbral, with particular reference to the formation of internal hearing and sense of rhythm.